Disaster Preparedness Sumatra Barat Community the Relationship with Natural Intelligence, Self Efficacy and Disaster Literacy - Suhardin Suhardin (Budapest International Research and Critics University, 2021)
West Sumatra is under the ring of fire and there are megathrusts, which come from two segments, namely the Siberut and Sipora-Pagai segments, earthquakes are part of people's lives, community preperedness in interacting and transacting with earthquakes is an unavoidable choice. This study seeks to examine, describe and analyze the relationship between variables of natural intelligence, self-efficacy and disaster literacy with disaster preparedness and analyze the dominant variables that influence disaster preparedness. The research method is quantitative associative correlation in analyzing the effect of one independent variable on the dependent variable. The results of the study found that first, there is a very significant positive relationship between natural intelligence and disaster preparedness; the second, there is a very significant positive relationship between self efficacy and disaster preparedness; the third, there is a very significant positive relationship between disaster literacy and disaster preparedness. From the findings of this study, it can be concluded that the community already has preparedness in dealing with earthquake disasters, but there is still a need for improvement, effective improvement by intervening on natural intelligence because this variable has proven to have a high influence on disaster preparedness.